Clinical progress of nanomedicine-based RNA therapies - Siyoung A. Lim; Alysia Cox; Madelynn Tung; Eun Ji Chung (Bioactive Materials, 2022)
The clinical application of nanoparticles (NPs) to deliver RNA for therapy has progressed rapidly since the FDA approval of Onpattro® in 2018 for the treatment of polyneuropathy associated with hereditary transthyretin amyloidosis. The emergency use authorization or approval and widespread global use of two mRNA-NP based vaccines developed by Moderna Therapeutics Inc. and Pfizer-BioNTech in 2021 has highlighted the translatability of NP technology for RNA delivery. Furthermore, in clinical trials, a wide variety of NP formulations have been found to extend the half-life of RNA molecules such as microRNA, small interfering RNA, and messenger RNA, with limited safety issues. In this review, we discuss the NP formulations that are already used in the clinic to deliver therapeutic RNA and highlight examples of RNA-NPs which are currently under evaluation for human use. We also detail NP formulations that failed to progress through clinical trials, in hopes of guiding future successful translation of nanomedicine-based RNA therapeutics into the clinic.